Characterisation and in vitro antimicrobial potential of liposome encapsulated silver ions against Candida albicans. (17th February 2016) - Low, W. L.; Kenward, M. A.; Hill, D. J.; Martin, C.
Abstract: Liposomes are biocompatible, biodegradable, controlled delivery systems with the ability to encapsulate both lipophilic and hydrophilic compounds, including metal ions. Liposome encapsulated Ag + (lipo-Ag + ), prepared by reverse-phase evaporation, was used as a controlled delivery system against Candida albicans . Characterisation of the lipo-Ag + indicated that the multilamellar vesicles with diameters ranging between ≈ 0.5 and 5.0 μm showed potential as a controlled delivery system to consistently deliver Ag + to C. albicans . Results from inductively coupled plasma (ICP) analysis showed higher association of cell bound Ag + at 15 mins post exposure when compared to unencapsulated Ag + . Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) indicate detrimental effects of Ag + on C. albicans cell structure. These effects along with the ICP results also correlate with previously reported time kill experiment observations.